Improving Health and Safety Performance of Construction through Lean Construction in Ghana : Drivers, Enablers and Constraints (International Journal of Scientific Research in Science and Technology, 2024)
The aim of this paper was to see how lean technology may be applied to improve safety and health performance in Ghana’s building construction sector. A structured questionnaire was used to gather data from civil/structural engineers, architects, construction managers, services engineers, and quantity surveyors that work in the construction industry. The sample was chosen using the purposeful sampling technique, taking into account the construction experts’ years of experience. The findings reveal that, building construction projects in Ghana may perform better if lean construction methods are applied correctly. Based on this finding, it is recommended that training, planning and proper layout of construction site so as to eliminate overlapping of movements on site, and building trust in working relations and working together as an effective team where the key strategies for improving health and safety performance of projects through lean construction technology.